USP8 regulates mitophagy by removing K6‐linked ubiquitin conjugates from parkin. (12th September 2014) - Durcan, Thomas M; Tang, Matthew Y; Pérusse, Joëlle R; Dashti, Eman A; Aguileta, Miguel A; McLelland, Gian‐Luca; Gros, Priti; Shaler, Thomas A; Faubert, Denis; Coulombe, Benoit; Fon, Edward A
Abstract Mutations in the Park2 gene, encoding the E3 ubiquitin‐ligase parkin, are responsible for a familial form of Parkinson's disease (PD). Parkin‐mediated ubiquitination is critical for the efficient elimination of depolarized dysfunctional mitochondria by autophagy (mitophagy). As damaged mitochondria are a major source of toxic reactive oxygen species within the cell, this pathway is believed to be highly relevant to the pathogenesis of PD. Little is known about how parkin‐mediated ubiquitination is regulated during mitophagy or about the nature of the ubiquitin conjugates involved. We report here that USP8/UBPY, a deubiquitinating enzyme not previously implicated in mitochondrial quality control, is critical for parkin‐mediated mitophagy. USP8 preferentially removes non‐canonical K6‐linked ubiquitin chains from parkin, a process required for the efficient recruitment of parkin to depolarized mitochondria and for their subsequent elimination by mitophagy. This work uncovers a novel role for USP8‐mediated deubiquitination of K6‐linked ubiquitin conjugates from parkin in mitochondrial quality control.